Modeling the organizational willingness for cross-sector collaboration in disaster risk management planning - Flores, Reymund Botin
Collaboration is commonly found in the area of human services. It can be a process operating in multijurisdictional and multiorganizational arrangements to address problems which cannot to be handled by a single organization. To achieve meaningful collaboration, however, organizations from separate sectors must overcome barriers related to organizational boundary maintenance. This paper describes the extent of willingness to collaborate of organizations across sectors of governance to plan for disaster preparedness. It explored the significant indicators of this willingness (unwillingness) to collaborate, taking inspiration from Ajzen’s Theory of Planned behavior and having decisionmakers from select local government units and nongovernment organizations as participants to the study. It employed structural equation modeling to assess and identify simultaneously the relationships among exogenous and endogenous variables and measure the fitness of the structural model of willingness to collaborate. Among others, the study confirmed that having the intention to collaborate would more likely result to organizational willingness. It also revealed that other than the organizations’ intention, there were other factors affecting the willingness to collaborate for disaster risk management (DRM) planning. It was found out that if the organization believes that other would-be co-collaborators can be trusted to deliver what are expected of them for DRM planning, they would be willing to join in this collaborative action. Previous collaboration experiences also mattered in the building of confidence. The higher positive belief based on previous collaboration experiences, the higher the possibility that they would be willing to collaborate for DRM planning with the other organizations, across sectors. However, there should be an enabling environment that would motivate the organizations to join the collaboration. Issues related to political, social, legal, and organizational that compromise their willingness need to be addressed.